(untitled) (Journal of Hama University, 2019)
Islamic architecture is a distinctive model with characteristics in its basic elements not found in other models. These elements are clearly visible in the old palaces and mosques of all kinds. Islamic architecture is only a basic element combined in a way that creates an artistic touch, And are characterized by a taste in terms of shape and place in the flat surface, and the organic relationship between the openings and the function behind them, which are in all architectural form the original Islamic style, it was clear in the interior and exterior of the buildings. In the last third of the twentieth century, things began to move towards an intellectual review of the architecture of modernity. In the past, it found an intellectual, functional and indispensable niche. The architects added symbols from the architecture of the past and heritage to some architectural facets of their projects. , And emerged a new era, which was called the postmodern era. In this paper, a comparison between the openings in the facades between the Islamic architecture in the Umayyad period and the postmodern architecture will be examined and the extent of the interaction between the two buildings will be determined.